A new species of Chiasmognathus from Kazakhstan (Hymenoptera: Apidae) - Engel, Michael S.; Packer, Laurence (Journal of Melittology, 2013)
A new species of the ammobatine bee genus Chiasmognathus Engel (Nomadinae: Ammobatini) is described and figured from near Almaty, Kazakhstan. Chiasmognathus scythicus Engel & Packer, new species, is superficially similar to C. gussakovskii (Popov), also from Central Asia (Tajikistan, Kyrgyzstan), but differs most notably in the form of the male genitalia